2012
DOI: 10.1074/jbc.m112.369355
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Regulation of the Protocadherin β Cluster during Her-2 Protein-induced Mammary Tumorigenesis Results from Altered N-Glycan Branching

Abstract: Background: Her-2-induced mammary tumor onset is significantly delayed in GnT-V knock-out mice. Results: The gene expression of the Pcdh␤ cluster is up-regulated in her-2-induced tumors with GnT-V deletion. Conclusion: Up-regulation of the Pcdh␤ cluster is one of the mechanisms for the reduced her-2-mediated tumorigenesis resulting from GnT-V deletion. Significance: Our findings shed new light on the molecular mechanisms of the effects of GnT-V on mammary tumorigenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 56 publications
(78 reference statements)
2
11
0
Order By: Relevance
“…In contrast, neither of these reported pathways was associated with TRIM44. Interestingly, microarray analysis showed that nine out of top 20 downregulated genes had oncogenic function ( C3AR1, FMN1, GBP1, ST3GAL5, NT5E, RAB27B, FBP2, HIPK3, PLAU , and 8 out of 20 top up‐regulated genes had tumor suppressive function ( NUPR1, CDK19, CADM1, INHBA, TNFSF10, PRKACB, PCDHB6, DDIT4 ). Furthermore, six of these eight tumor suppressive genes are associated with apoptotic mechanisms ( NUPR1 , CDK19, CADM1, INHBA, TNFSF10, DDIT4 ).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, neither of these reported pathways was associated with TRIM44. Interestingly, microarray analysis showed that nine out of top 20 downregulated genes had oncogenic function ( C3AR1, FMN1, GBP1, ST3GAL5, NT5E, RAB27B, FBP2, HIPK3, PLAU , and 8 out of 20 top up‐regulated genes had tumor suppressive function ( NUPR1, CDK19, CADM1, INHBA, TNFSF10, PRKACB, PCDHB6, DDIT4 ). Furthermore, six of these eight tumor suppressive genes are associated with apoptotic mechanisms ( NUPR1 , CDK19, CADM1, INHBA, TNFSF10, DDIT4 ).…”
Section: Discussionmentioning
confidence: 99%
“…The galectin interaction with branched N-glycans on integrins is associated with turnover and maturation of the FA, fibronectin fibrillogensis and actin microfilament remodelling (12,27). Knockdown of MGAT5 in cancer cells has been shown to reduce N-glycan branched on N-CAD and turnover of cell-cell adhesions, as well as cell migration (32). Removal of three sites with branched Nglycans from N-CAD did not alter surface expression but did reduced cancer cell migration and invasion.…”
Section: Discussionmentioning
confidence: 99%
“…However, the epitope for these antibodies were mostly designed against the protein moiety and not towards the N ‐glycan structures . To date, N ‐glycan based biomarkers or models have been developed to help validate diagnosis and evaluate outcomes for various cancers or other illnesses, including liver cancer , rectal carcinoma , ovarian cancer and lung cancer . Some reviews have highlighted the promising prospect of N ‐glycans as cancer biomarkers and the progress in glycomic research strategies recently .…”
Section: Discussionmentioning
confidence: 99%
“…Serum protein N ‐glycan analysis was performed using DSA‐FACE technology as described previously . Briefly, the N ‐glycans present on glycoproteins in 2 μL of serum were released with peptide N ‐glycosidase‐F (PNGaseF) (New England Biolabs, Boston, MA).…”
Section: Methodsmentioning
confidence: 99%